Hommage ; säveltäjät pianoteostensa tulkkeina - Englund, Einar; Hannikainen, Ilmari; Kokkonen, Joonas; Linko, Ernst; Merikanto, Oskar; Palmgren, Selim (Pianon ystävät, 2003)
14 kappaletta.
Keywords: historialliset äänitykset